Leadership Theory and Research A Critical Approach to New and Existing Paradigms - Harrison, Christian (Springer International Publishing, 2018)
'This is an ideal text for students and executives seeking an overview of existing leadership research and [...] insight into leadership practices in modern contemporary organisations.' -Denis Harrington, Head of Graduate Business, Waterford Institute of Technology, Ireland 'This work underscores how a growing range of literature on leadership acknowledges the key role of leadership for generating and sustaining effective organizational outcomes.' -Margaret Linehan, Head of School of Humanities, Cork Institute of Technology, Ireland 'Harrison demonstrates the diversity of leadership and the importance of its evolving perspectives.' -Kevin Burnard, Assistant Professor, Western Connecticut State University, USA 'An excellent text for undergraduates, postgraduates and MBA students. Full of great examples and case studies.' -Stuart Paul, Retired Lecturer in Leadership, University of the West of Scotland, UK This book provides a concise yet comprehensive literature review on leadership. As well as offering critical insight into leadership research, the author addresses emerging paradigms and identifies new approaches. A vital tool for leadership students and scholars, the text will enable readers to demonstrate a critical awareness of current developments both in theory and practice of leadership and its importance in modern organizations. Both scholars and practitioners will find the engaging discussion in this book particularly useful as the author offers practical ideas for development and a much-needed unified theory on leadership.